1968
DOI: 10.1161/01.cir.37.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Observation and Simulation of the Circulation, Acid-Base Balance, and Response to CO 2 in Cheyne-Stokes Respiration

Abstract: Circulatory, chemical, and ventilatory response factors in Cheyne-Stokes respiration (CSR) were studied by experimental procedures and by mathematical analysis. Hemodynamic, ventilatory, and blood gas patterns in 16 patients with heart disease and CSR (group A) and 16 patients with congestive heart failure (CHF) without CSR (group B) were compared. CO2 and oxygen were administered to group A. The phenomena exhibited by patients with CSR were simulated by a mathematical model.The following conclusions were draw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 16 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Increased circulation time from the lungs to the chemoreceptors could contribute to the pathogenesis of CSA-CSR. Indeed, an early study reported increased circulation time in patients with heart failure with CSA-CSR [105]. However, to induce CSA-CSR in dogs, GUYTON et al [106] had to artificially lengthen heart-to-brain circulation time far beyond physiological values of up to several minutes and even then induced CSA-CSR in only approximately one-third of the animals.…”
Section: Role Of Arousal From Sleepmentioning
confidence: 99%
“…Increased circulation time from the lungs to the chemoreceptors could contribute to the pathogenesis of CSA-CSR. Indeed, an early study reported increased circulation time in patients with heart failure with CSA-CSR [105]. However, to induce CSA-CSR in dogs, GUYTON et al [106] had to artificially lengthen heart-to-brain circulation time far beyond physiological values of up to several minutes and even then induced CSA-CSR in only approximately one-third of the animals.…”
Section: Role Of Arousal From Sleepmentioning
confidence: 99%